Pengembangan Kawasan Perdesaan Berkelanjutan Berbasis Potensi Pertanian - Siradjuddin, Irsyadi (REKA RUANG, 2023)
The village of Pa'rappunganta has a large agricultural area, but there is no sustainable agricultural zone development. Establishing a sustainable rural zone requires identifying the main crops and creating strategies and guidelines for sustainable rural zone development. The purpose of the research is to identify main crops and create strategies and guidelines for sustainable rural zone development in Pa'rappunganta village. The research was conducted from March to June 2019 using LQ, Shift Share, Classification Typology, and SWOT analysis methods. The results showed that the main crop is sugarcane, while corn and chili are the secondary crops. Sugarcane is used to supply the Takalar Sugar Factory, while corn and chili are consumed by households and also supplied to other areas for food and horticulture needs. The strategy for developing Pa'rappunganta village as a sustainable agricultural zone is by developing the potential sector, which is the agricultural sector (sugarcane, corn, and chili), as it has suitable land resources. The guidelines for development in Pa'rappunganta village include the establishment of agroindustrial infrastructure, empowering the community, developing basic crops and high-value crops to increase export value outside the region, diversifying agricultural products to increase sales value, and establishing rural zone organizations/communities.